Facile synthesize of transparent hydrophobic nano- CaCO3 based coatings for self-cleaning and anti-fogging - Syafiq, A.; Vengadaesvaran, Balakrishnan; Ahmed, Usman; Rahim, Nasrudin Abd; Pandey, Adarsh Kumar; Bushroa, Abdul Razak; Ramesh, Kasi; Ramesh, Subramaniam (Elsevier, 2020)
The research work was conducted to synthesize transparent self-cleaning coatings by using organic Polydimethylsiloxane (PDMS) polymers and inorganic nano-Calcium carbonate (CaCO3) fillers that can be fabricated easily on the glass panel via spray-method and cured under room temperature. The coating system has been developed with a low-cost nano-CaCO3 and simple process which is targeted to keep the cost at lower side. The self-cleaning and durability of nano-CaCO3 coating systems after 4 month of outdoor exposure have been investigated. From the obtained result, the transmission of 0.8 wt % of nano-CaCO3 coated substrate was slightly degraded by 7% only indicating that its excellent self-cleaning effect. Higher loading ratio of nano-CaCO3 contributes to larger capillary pressure (Pc) and air-pockets which have deteriorated the water hammer pressure of rainfall impact (PWH) and fog. Therefore, the Water Contact Angle (WCA) of coating system was degraded by 2% only and exhibits a great anti-fog property. © 2019 Elsevier B.V.